Juvenile Delinquency in India: Comparative Study - K Pattnaik, Prabir; Mishra, Itishree (International Journal of Psychosocial Rehabilitation, 2025)
Contemporary World has observed an increase in the rate of juvenile crime, which is an extremely serious issue, particularly in India, as these juveniles are their respective countries' future. Children who are not given proper guidance and who are in not a good influence are turning towards the criminal direction to lead their lives. Different factors are responsible for this juvenile approach. This work explores all aspects of Juvenile Delinquency in Major Countries and steps taken by these countries to tackle offenses committed by juveniles and further compare their laws for dealing with juveniles in India. This research paper also aims at studying the major differences between the Juvenile Justice Act, 2000 and Juvenile Act, 2015 which is recently passed Act relating to Juvenile in the Parliament. The goal of the research is to get the best way to deal with juveniles by comparative study among the major countries.